Islamic Philanthropy Research Trends on Zakat Infaq and Waqf Based on Bibliometric Mapping 2000–2024 - Judijanto, Loso (West Science Islamic Studies, 2026)
This study examines the development and intellectual structure of Islamic philanthropy research focusing on zakat, infaq/sadaqah, and waqf (ZISWAF) over the period 2000–2024 using a bibliometric approach. Drawing on peer-reviewed publications indexed in major academic databases, the study applies science mapping techniques— including keyword co-occurrence, overlay visualization, density mapping, co-citation, and collaboration analysis—using VOSviewer. The findings reveal a significant growth and diversification of the literature, with waqf emerging as the central and most influential theme, closely connected to Islamic microfinance, cash waqf, economic recovery, and sustainable development. Temporal analysis indicates a clear thematic shift from early discussions on microfinance and charitable redistribution toward more recent emphases on Islamic social finance, SDGs, food security, and post-crisis economic resilience. The intellectual structure of the field is shaped by a relatively small group of influential authors and institutions, predominantly based in Indonesia, which also acts as the main hub of international collaboration.